Timeless Ideas of Maria Grzegorzewska in Contemporary Special Pedagogy and Education in Poland - Malwina Maria Kocoń; Natalia Malik (Maria Curie-Skłodowska University, Lublin, Poland, 2023)
Introduction: The life and multifaceted activity of Maria Grzegorzewska (1887-1967) are a valuable historical source. However, what is most invaluable in the work of the precursor of Polish special pedagogy is the timelessness of her ideas, the echoes of which still resound today. Research Aim: The article attempts to indicate the influence of Maria Grzegorzewska on the development of modern pedagogical science and practice. Evidence-based Facts: Not only the scientific, organizational and educational activities of Maria Grzegorzewska, concerning surdopedagogy, oligophrenopedagogy and pedeutology, but also her views, which have a timeless character, were brought closer. Summary: It has been shown that despite the passage of time, Maria Grzegorzewska's pedeutological, deontological, and axiological concepts have not lost their relevance, because they are based on universal values that are the foundation of the teacher-educator's work.